2021
DOI: 10.3390/nu13062045
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lifestyle and Diet on Gut Microbiota Composition, Inflammation and Muscle Performance in Our Aging Society

Abstract: Living longer is associated with an increased risk of chronic diseases, including impairments of the musculoskeletal and immune system as well as metabolic disorders and certain cancers, each of which can negatively affect the relationship between host and microbiota up to the occurrence of dysbiosis. On the other hand, lifestyle factors, including regular physical exercise and a healthy diet, can affect skeletal muscle and immune aging positively at all ages. Accordingly, health benefits could partly depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 272 publications
0
50
0
1
Order By: Relevance
“…First, we measured the symptoms of anxiety and depression with the GAD-7 and PHQ-9 in the past 2 weeks. Second, the intestinal flora was greatly influenced by diet, lifestyle, geography, and age, and the composition was dynamic and fluctuating ( 41 , 42 ). Large-scale population studies found that antibiotics used in anti-infective treatment significantly increased the risk of individual psychological diseases such as anxiety and depression ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, we measured the symptoms of anxiety and depression with the GAD-7 and PHQ-9 in the past 2 weeks. Second, the intestinal flora was greatly influenced by diet, lifestyle, geography, and age, and the composition was dynamic and fluctuating ( 41 , 42 ). Large-scale population studies found that antibiotics used in anti-infective treatment significantly increased the risk of individual psychological diseases such as anxiety and depression ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise/physical activity is a crucial component of any strategy designed to prevent and/or treat sarcopenia, which may be mediated, in part, by modulating the gut microbiome ( Strasser et al, 2021 ). Accordingly, the impact of exercise training in modulating the gut microbiota has primarily been established in physically active populations and animal models in the context of aerobic-based exercise ( Cerdá et al, 2016 ; Taniguchi et al, 2018 ; Morita et al, 2019 ; Przewłócka et al, 2020 ; Clauss et al, 2021 ).…”
Section: Exercise As a Strategy To Counter Anabolic Resistance Via The Modulation Of Gut Microbiotamentioning
confidence: 99%
“…Aging reduces the biodiversity of human gut microbiota and the abundance of Bifidobacteria , Lactobacilli , and short chain free fatty acids (SCFAs) producers, such as Faecalibacterium prausnitzii , Eubacterium spp., Roseburia spp., and Ruminococcus spp. [ 13 ]. Studies carried out in China and Italy separately report that microbial community richness contributes to longevity [ 14 , 15 ].…”
Section: Microbiota In Aging Drosophilamentioning
confidence: 99%